2010
DOI: 10.1088/1742-6596/254/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

From SICs and MUBs to Eddington

Abstract: This is a survey of some very old knowledge about Mutually Unbiased Bases (MUB) and Symmetric Informationally Complete POVMs (SIC). In prime dimensions the former are closely tied to an elliptic normal curve symmetric under the Heisenberg group, while the latter are believed to be orbits under the Heisenberg group in all dimensions. In dimensions 3 and 4 the SICs are understandable in terms of elliptic curves, but a general statement escapes us. The geometry of the SICs in 3 and 4 dimensions is discussed in so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Theorems 1, 3, and 4 also establish a one-toone correspondence between SICs and NQPRs of quantum mechanics with minimal negativity, namely, perfect QPRs. Based on the study of SICs [19][20][21][22][23], we can construct perfect QPRs at least in dimensions 2 to 16,19,24,28,31,35,37,43,48, and with extremely high precision up to dimension 67 (the number of known solutions is increasing continually). There is every reason to believe that such representations exist for any Hilbert space of finite dimension.…”
Section: Theorem 4 the Channel Negativity Of Any Nqprmentioning
confidence: 99%
“…Theorems 1, 3, and 4 also establish a one-toone correspondence between SICs and NQPRs of quantum mechanics with minimal negativity, namely, perfect QPRs. Based on the study of SICs [19][20][21][22][23], we can construct perfect QPRs at least in dimensions 2 to 16,19,24,28,31,35,37,43,48, and with extremely high precision up to dimension 67 (the number of known solutions is increasing continually). There is every reason to believe that such representations exist for any Hilbert space of finite dimension.…”
Section: Theorem 4 the Channel Negativity Of Any Nqprmentioning
confidence: 99%
“…The symmetric group S 3 contains the permutation matrices I, X and X 2 of the Pauli group, where X = Taking the eigensystem of the latter matrices, it is not difficult check that there exists two types of qutrit magic states of the form (0, 1, ±1) ≡ 1 √ 2 (|1 ± |2 ). Then, taking the action of the nine qutrit Pauli matrices, one arrives at the well known Hesse SIC [10,11,12].…”
Section: Permutation Gates Magic States and Informationally Completementioning
confidence: 99%
“…Hughston [20] has shown that the SIC vectors of the single SIC for t = 0 can be obtained from the inflection points of a family of cubic elliptic curves on the complex projective plane known as the Hesse pencil (see also Bengtsson [21].) There are 8 SICs with parameter value t = π 9 that are unitarily equivalent to the single SIC for t = 0, and we call these 9 SICs the Hesse SICs.…”
Section: Properties Of Weyl-heisenberg Qutrit Sicsmentioning
confidence: 99%